Clinical concepts for cabazitaxel in the management of metastatic castration‐resistant prostate cancer. Issue 6 (16th July 2019) - Al‐Mansouri, Loma; Gurney, Howard
Abstract: Prostate cancer is the most common malignancy in male patients. The second‐generation taxanes, cabazitaxel, is a therapeutic option with an overall survival advantage for patients with metastatic castration‐resistant prostate cancer. This review explores specific aspects of cabazitaxel including the duration of treatment, the efficacy of lower dose and effect on the incidence of adverse effects, and optimal sequencing of cabazitaxel. A systematic search of data baselines "PubMed, Ovid Medline, Scopus, and Embase" was carried out using the keywords "cabazitaxel" and "metastatic prostate cancer." The search was limited to clinical studies performed after October 2010 addressing duration of treatment, the efficacy of lower dose, adverse effects, the sequence of cabazitaxel in relation to other lines of therapy and use in chemotherapy naïve patients. The current evidence supports the utility and safety of cabazitaxel as either a second‐ or third‐line agent after docetaxel, or as an alternative to docetaxel in the chemotherapy‐naive setting. Extended duration of cabazitaxel beyond 10 cycles is feasible and does not appear to lead to cumulative toxicity. In conclusion, cabazitaxel can improve survival in castrate‐resistant prostate cancer with an acceptable risk of toxicity. Studies confirmed the efficacy of reduced dose and utility in patients without prior chemotherapy.